Strategi Alternatif Pemecahan Konflik Melalui Pembinaan Nilai-Nilai Kearifan Lokal dalam Tradisi Lisan: - I Wayan Nitayadnya (Kantor Bahasa Provinsi Maluku Utara, 2014)
There are tradition value shifting and culture awareness fading in Poso and Palu which becomes one ofmany reason behind the conflict on those cities. According to that point, one of strategic step whichshould be taken is to explore the local wisdom which has existed on the local literature because the local wisdom has commonly established the literature. The exploration needs to be introduced, not only to theliterature society but also to the common. This step must be done in order that the common society could understand the local wisdom of the cities. There are some alternative strategies which can be taken to minimalize the conflict in the area. Those are education guiding based on local wisdom, optimalizing the function of mass media in socializing local wisdom, increasing the function of art communities in exploring the local wisdom, and increasing the funtion of government institution in implementing the local wisdom.